Obtenção e caracterização de lipossomas unilamelares pequenos contendo cafeína - Chorilli, Marlus [UNESP]; Rimério, Thereana Cristina [UNESP]; Oliveira, Anselmo Gomes de [UNESP]; Scarpa, Maria Virgínia [UNESP] (My University, 2007)
Due to great difficulty of penetration of drugs through skin, different organized systems, such as liposomes, have been studied in order to increase percutaneous penetration. The aims of this work were to obtain and characterize small unilamellar liposomes containing caffeine (CAF). Liposomes composed by soy phosphatidylcholine - PS (40 mM) or hydrogenated PS - PSH (40 mM), with and without cholesterol - CHO (6 mM) and CAF (30 mg/mL), were characterized by size distribution, determination of mean diameter and encapsulation efficiency. Uniform size distribution with low polidispersity was observed. The mean of diameters obtained were: PS/CHO (64 nm), PS (80 nm), PSH/CHO (85 nm), PS/CAF (145 nm), PS/CHO/CAF (147 nm), PSH/CHO/CAF (152 nm), PSH (166 nm) and PSH/CAF (481 nm). The obtained encapsulation efficiency was 10.84% for PSH/CHO/CAF, followed by PS/CHO (6.61%), PSH/CAF (3.07%) and PS/CAF (1.57%).
Obtaining and characterization of small unilamellar liposomes containing caffeine
Keywords: Caffeine; Encapsulation efficiency; Mean diameter; Small unilamellar liposomes; caffeine; cholesterol; liposome; phosphatidylcholine; encapsulation; particle size